National Food Safety Control Systems In Sub-Saharan Africa: Does Uganda’s Aquaculture Control System Meet International Requirements - Bagumire, Ananias; Todd, Ewen C.D.; Muyanja, Charles; Nasinyama, George W. (Food Policy, 2009)
Stringent food safety requirements set by developed country markets, which require exporting countries to establish effective national food control systems (NFCS) that guarantee safety of the products to the market, pose a challenge to Sub-Saharan countries in development of aquaculture products as alternative exports following the decline of capture fisheries. In the study, four components of Uganda’s NFCS including legislation, competent authority, inspection services, and laboratory services were evaluated for compliance with FAO/WHO, European Union (EU), and the United States (US) market recommendations for guaranteeing aquaculture product safety. Using a checklist, component elements were benchmarked and scored, and components ranked for compliance with the recommendations. On a scale of 0–5, where 0 denotes none, 1 very low, 2 low, 3 some, 4 almost total, and 5 full compliance, only laboratory services had a barely acceptable score of 3.3 (some compliance). The rest including legislation which is central in setting the level of controls by the other three components scored below three, and the combined score for all components was only 2.2, indicating that Uganda’s NFCS was still short of the requirements to allow entrepreneurs to access markets in the EU and other developed countries. The low score is partly attributed to the dynamics of this country’s fledgling aquaculture industry and the rapidly evolving food safety requirements in the international markets.
Keywords: National food control system; Aquaculture; Compliance; International requirements; Uganda; Sub-Saharan Africa